Applicability of the Lean methodology in a hospital laundry - Campo Alves da Cunha, Ana Maria; de Campos, Carlos Eduardo; Hismon Castellon Rifarachi, Humberto (O Mundo da Saúde, 2011)
Abstract: The Lean methodology has been largely studied and used by companies worldwide. It seeks to eliminate the process waste by rendering speed and reducing the total time of the service provided, while improving the result quality. This paper aims at evaluating the applicability of using the Lean methodology in a hospital laundry. A case study was employed with a quantitative research by developing the implementation project of the Lean methodology in the work process of a hospital laundry. The result was the creation of a continuous flow by standardizing the processes that allowed the inventories to be reduced, improved the productivity and decreased the lead time. All the resulting improvements directly impacted on reducing the costs involved in the processing of hospital clothes. Although the quantification of the results justifies the methodology application to develop improvement projects, the main and higher gain is changing behaviors and attitudes of the employees in a favorable environment that allows everybody to express their competencies totally by means of a continuous improvement view.